A discussion on methodologies in identifying the maintenance criteria of green roof in high-rise buildings / Shafikah Saharuddin ... [et al.] - Saharuddin, Shafikah; Mohd Roshdi, Farrah Rina; Mohd Yusof, Nur Fatiha (2021)
Numerous problems arise due to the development growth of a country such as the destruction of natural environments and the deficit in green spaces. Thus, in order to overcome these issues, one of the sustainable approaches in a green building that can be implemented is the green roof. The utilization of a green rooftop over structures has gradually turned into a pattern in urban communities as it gives various advantages to the nation. Unfortunately, the maintenance consideration is still largely unexplored and often being neglected during the planning stage of the green roof implementation. In view of this, this project was initiated to establish maintenance best practice of green roof for high-rise residential, with criteria identification and ranking. This paper presents the methodologies proposed in analyzing the criteria of maintenance in approaching towards the establishment of the maintenance best practice for green roof, by concentrating on high-rise buildings. The data were collected from intensive literature from journals and articles in Malaysian and international contexts. The result of the study discovers past experiences in green roof implementation which leads to the establishment of best practice maintenance for this research.